Optimisation of electrical discharge machining for oxidation-free metallic nanoparticle synthesis of titanium alloy - Irshad Ahamad, Khilji (2023)
Various materials and chemical synthesis techniques have been investigated to develop better-quality nanoparticles with uniform shapes, sizes, dimensions, and dynamic properties. The development of defined nanoparticles (NP) with specific properties is still in search; therefore, in the present work, an approach using electrical discharge machining (EDM) to generate nanoparticles is investigated. The established EDM process has been used to generate uniform nanoparticles with efficient surface-related properties. Electrical discharge machining is a widely used manufacturing process for producing precise and detailed parts, particularly dies, moulds, and other complex shapes. This process involves using an electrode to generate electrical discharges through a workpiece, melting and vaporising the material to achieve the desired shape. In recent years, this area has seen significant advances in improved surface finishing, greater flexibility and Increased accuracy and precision. These advancements have made EDM an even more valuable tool for a wide range of industries and enabled the production of high-quality parts with greater efficiency and precision. As a result of new advancements, this machine can synthesise nanoparticles in the form of waste derbies. In just the past few years, this has emerged as a phenomenon of exceptional interest for nanoparticle synthesis by EDM. It is generally agreed that EDM can synthesise nanoparticles. However, this is a matter of ongoing discussion and further optimisation and update. Some researchers have attempted to solve these problems, which are still under investigation. The present work proposes a simple way to address this issue using an optimisation process and to add oleic acid as a capping agent with dielectric and synthesis nanoparticles of titanium and copper. These results were measured using SEM, TEM, XRD, TGA/DTA and FT-IR approaches. These methods have demonstrated a marked improvement in the quality of material synthesis and produced oxidation-free nanoparticles. In synthesising Ti alloys and copper by electrical discharge machining, the main parameters affecting the synthesis were current, on-time, off-time, and tool gap. The present study was conducted using the RSM experimental design to develop NPs. The experimental findings and optimisation results, a current of 6A, a pulse-on time of 60 ns, a pulse-off time of 40 ns, and kerosene as the dielectric, enabled the fabrication of 10 mm to 20 μm spherical nanoparticles of titanium alloy and copper. High voltage was used to produce 100 to 200 μm sized particles. Oleic acid was used on the surface as a covering agent for the dielectric fluid to obtain oxidation-free particles. SEM Exhibit result of average 20 μm spherical size of particles and EDX revealed no other elements associated. FT-IR graph represents a functional group of oleic acid as a capping agent that prevents the particle from oxidation. XRD characterised the structural properties of synthesised particles to remain the same as before. No crystalline structure changes or phase changes are detected in the material property.